Rapid and sensitive methodology for determination of ethyl carbamate in fortified wines using microextraction by packed sorbent and gas chromatography with mass spectrometric detection - Leça, João M. (2021)
This work presents a new methodology to quantify ethyl carbamate (EC) in fortified wines. The presented approach combines the microextraction by packed sorbent (MEPS), using a hand-held automated ana lytical syringe, with one-dimensional gas chromatography coupled with mass spectrometry detection (GC–MS). The performance of different MEPS sorbent materials was tested, namely SIL, C2, C8, C18, and M1. Also, several extraction solvents and the matrix effect were evaluated. Experimental data showed that C8 and dichloromethane were the best sorbent/solvent pair to extract EC. Concerning solvent and sample volumes optimization used in MEPS extraction an experimental design (DoE) was carried out. The best extraction yield was achieved passing 300 L of sample and 100 L of dichloromethane. The method validation was performed using a matrix-matched calibration using both sweet and dry fortified wines, to minimize the matrix effect. The proposed methodology presented good linearity (R2 = 0.9999) and high sensitivity, with quite low limits of detection (LOD) and quantification (LOQ), 1.5 g L−1 and 4.5 g L−1, respectively. The recoveries varied between 97% and 106%, while the method precision (repeatability and reproducibility) was lower than 7%. The applicability of the methodology was confirmed through the analysis of 16 fortified wines, with values ranging between 7.3 and 206 g L−1. All chromatograms showed good peak resolution, confirming its selectivity. The developed MEPS/GC–MS methodology arises as an importanttoolto quantify EC in fortified wines, combining efficiency and effectiveness, with simpler, faster and affordable analytical procedures that provide great sensitivity without using sophisticated and expensive equipment.